2015
DOI: 10.4000/res.691
|View full text |Cite
|
Sign up to set email alerts
|

La reconfiguration des récits postsocialistes de Nowa Huta (Pologne) et de Dunaújváros (Hongrie)

Abstract: In June 2014, for just a few days, a statue of Lenin returned to Nowa Huta, close to the spot where once a huge monument of Lenin used to stand, dominating this socialist city visually (but not only so). 1 The statue that 'returned' was small, less than half-a-meter tall and made of bright kitschy, greenish plastic: 2 it was peeing in the same manner as the Manneken-Pis in Brussels. And yet the installation of the statue which proved popular with passers-by, was enough for two members of the main opposition Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Urban identity building reflects also interaction between hierarchical levels of territorial identity, which often is well-accentuated in post-socialist societies. Jansen, S. (2001) and Zechenter, K. (2015) suggested that the symbolic success of post-socialist cities depends on aligning the city's identity with the general prevalent understanding of national identity. However, there is evidence that in post-socialist countries local urban identity, due to some reason, may run counter to the national identity, as it happened in Sevastopol before the annexation of Crimea (Qualls, K.D.…”
Section: Introductionmentioning
confidence: 99%
“…Urban identity building reflects also interaction between hierarchical levels of territorial identity, which often is well-accentuated in post-socialist societies. Jansen, S. (2001) and Zechenter, K. (2015) suggested that the symbolic success of post-socialist cities depends on aligning the city's identity with the general prevalent understanding of national identity. However, there is evidence that in post-socialist countries local urban identity, due to some reason, may run counter to the national identity, as it happened in Sevastopol before the annexation of Crimea (Qualls, K.D.…”
Section: Introductionmentioning
confidence: 99%